PENGARUH KEPUASAN KERJA DAN KARAKTERISTIK PEKERJAAN TERHADAP KOMITMEN KARYAWAN DI PT. DELTA INTERNUSA PEKANBARU - Muhammad Rizki; Susi Hendriani; Kurniawaty Fitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research held in PT. Delta Internusa Pekanbaru in order to analyze the influence of job satisfaction and job characteristics to employees’ commitment. Population are all employees, consist of 53 people among all division. Considering the number limitation so sampling method used is census that covers all employee as the respondents. Data analyzed by using multiple linier regression analysis by using SPSS 17 for windows.Result of this study shows that both job satisfaction and job characteristics significantly influence, either in simultenously or partially, to employees’ commitment. Among both independent variables, employee’s commitment is more dominant effected by job satisfaction rather than job characteristics. It is recommended to company determine a transparant indicator of career development, creating a comfort work-space and conducting a consistant employee development program. It is also recommended to hold temporary job rotation among all employees on to other division.Keywords: Job Satisfaction, Job Characteristic and Employee’s Commitment